The Use of Digital Technology in Marketing Strategies to Attract Visitors' Intention: A Case Study of Penglipuran Tourist Village, Bali - Setiawan, Anugrah Rega; Azizah, Fadilla Nur; Aprilya, Rani; Lestari, Rahayu; Hardini, Resti; Digdowiseiso , Kumba (CV ODIS, 2023)
In the era of growing digitalization, digital-based marketing strategies have become a key component in increasing the attractiveness and competitiveness of tourist destinations. Penglipuran Tourism Village is one of the tourist destinations in Bali which has potential and is unique and attractive to tourists. Therefore, this research aims to analyze the marketing strategies implemented in Penglipuran Village Tourism and the extent to which the use of digital technology can contribute to increasing tourist visits. The research method used is qualitative by collecting data through observation and analysis of related documents. The research results show that the marketing strategy for Penglipuran Village Tourism involves the use of social media, websites, online advertising, user-generated content (UGC), and Google Business as channels to promote and communicate the attractions and activities in the tourist village. Creative content such as photos, videos, and interesting stories are used to attract tourist interest. Direct interaction with tourists via social media and being responsive to questions and responses is also an important part of the marketing strategy. The use of digital technology in marketing Penglipuran Village Tourism has had a significant positive impact, such as (1) Tourist visits have increased; (2) The use of social media, websites, online advertising, and user-generated content (UGC) has expanded the reach of promotions and (3) increased tourist awareness about the beauty and potential of the Penglipuran Village Tourism. Thus, the combination of the use of digital technology and marketing strategies has become the key to success in marketing the Penglipuran Village Tourism, inviting tourist interest and increasing the number of tourist visits.